Academic procrastination in the area of Physics in university students (Revista Innova Educación, 2020)
In order to describe the academic procrastination in the Physics area of a university population in Cojedes Venezuela, the present study was carried out. For its preparation, there were students corresponding to the Telecommunications Engineering career of the National Polytechnic Experimental University of the Armed Forces Nucleus Cojedes, students of Physics I and Physics III subjects. The methodology used was a non-experimental design, with field research and descriptive level. The population was 43 students, with whom an observation guide was used in the first instance as an instrument. For interviews and questionnaires, a sample of eight students was taken, corresponding to 18.6% of the population. Among the most relevant results, it was found that more than 60% of the participants exhibited procrastinating behaviors. It was also observed that the majority prepared with little advance for the evaluations and stated that they felt comfortable this way, because "they work better under pressure". As a conclusion, it was possible to verify that there is a presence of academic procrastination in the majority of the population, although it is an active procrastination.
Keywords: time management; procrastination; academic procrastination; academic tasks